Observations on nest reuse by birds in the trunk of Syagrus romanzoffiana (Cham.) Glassman (Arecaceae) in the Protected Área of Alto do Iguaçu (Nova Iguaçu, Rio de Janeiro State, Brazil) - Vantil, Soraya Vieira; Fonseca, Yuri Borba da; Guedes, Patricia Gonçalves; Pereira da Silva, Shirley Seixas (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2024)
We report observations of different bird species’ nest reuse in Syagrus romanzoffiana (Queen Palm) in Nova Iguaçu, Rio de Janeiro. Data collected from 2017 to 2020 show occupation of the palm openings by the following species: Ramphastos toco, Melanerpes candidus, Amazona amazonica, Troglodytes musculus, Psittacara leucophthalmus, and Primolius maracana. There are few reports on the reuse of the same nest by different species of neotropical birds. In addition to the records presented, the study highlights the importance of S. romanzoffiana for the reproduction of birds in the Atlantic Forest in addition to other key species of flora associated with the maintenance of native fauna.
Keywords: Nesting; Queen palm; Birds; Atlantic Forest